(untitled) (Global Journal of Medical Research, 2017)
The National Surgical Quality Improvement Program (NSQIP) is a data collection system used to track hospital and surgical performance and to compare hospital and surgical quality. Improvement in quality metrics, both over time in the same institution and against peer hospitals, is rewarded by financial incentives with improved Medicare payments. As such physicians may be interested in the quality metrics of their specific practice and performance improvement not only because of the possibility of improved care provision but also because reimbursement may become dependent on such data. We hypothesized that involvement of general surgery residents would be a useful modality to improve NSQIP data and possibly improve patient care. The residents were incorporated into our hospital performance committee and directly assisted with the overhaul of surgical quality assurance over an eight-month period. Data from the antecedent eight-month period was compared to data from the eight months after general surgery resident oversight was initiated. Statistically significant improvement in hospital performance was demonstrated in five of the eight measured categories. We believe that this finding could be reproducible in other institutions; additional studies are necessary to determine this.